Comparative Study between Melatonin and Progesterone -PMSG on Onset of Ovarian Activity in an Estrous EWES - Al-Tayeb , A.M.; Hussein, Khawla. A. (International Journal of Psychosocial Rehabilitation, 2020)
A study was conducted on 30 adult Iraqi ewes and 6 fertile rams. Ewes were divided into 3 groups 10 animals each, first group treated with melatonin implants (18 mg / animal) for 30 days, second group was treated with intra-vaginal sponges for 10 days followed by injection of PMSG (500 IU / IM) at the time of sponges withdrawal, third group was injected with distilled water (1 ml / IM) and considered as control group. Blood samples were collected from all ewes for estimation of progesterone concentrations at 2 hours before treatments, 7 days after treatments, at 0, 15, 30, 45, 60, 75 and 90 days of gestation. Duration of estrous phase in group 2 (21.9 ± 1.48) was appeared significantly (P≤0.05) higher as compared with group one and group three (18.8 ± 0.43, 17.7 ± 0.88) respectively. Single pregnancy rates (82.40%) were significantly (P≤0.01) increased as compared with twining rates (17.60%). The conception rates in group 2 (80%) significantly (P≤0.01) increased as compared with group 1 and 3 (60 and 30 %) respectively. The lambing and fertility rates in group 2 (125%) appeared significantly (P≤0.01) higher as compared with group 1 and 3 (116.7% and 100%) respectively. In nature of parturition there was no significant difference among treated groups, while in total percentage sex of lambs, male newborn was (65%) significantly (P≤0.01) higher as compared with female newborn (35%). In conclusion the administration of progesterone to ewes by intra-vaginal sponges gave a good results in estrus synchronization, pregnancy rate, lambing rate particularly when it was used with PMSG.